Acellular mineralized allogenic block bone graft does not remodel during the 10 weeks following concurrent implant placement in a rabbit femoral model. Issue 1 (10th October 2019) - Cohen, D. Joshua; Scott, Kayla M.; Kulkarni, Aniket N.; Wayne, Jennifer S.; Boyan, Barbara D.; Schwartz, Zvi
Abstract: Objectives: Due to bone loss, endosseous implants often require addition of a bone graft to support adequate primary fixation, bone regeneration, and osseointegration. The aim of this study was to compare effectiveness of autogenic and allogenic bone grafts when used during simultaneous insertion of the implant. Materials and Methods: 4‐mm‐diameter rabbit diaphyseal bone autografts or allografts ( n  = 16/group) with a 3.2‐mm pre‐drilled hole in the center were placed into a 4 mm defect in the proximal femur of 3.5 kg male New Zealand White rabbits. Machined 3.2 × 10 mm grit‐blasted, acid‐etched titanium–aluminum–vanadium (Ti6Al4V) implants were placed. Control implants were placed into progressively drilled 3.2‐mm holes in the contralateral limbs. Post‐insertion day 70, samples were analyzed by micro‐CT and calcified histology, or by mechanical torque and push‐out testing followed by decalcified histology. Results: Both grafts were integrated with the native bone. Micro‐CT showed less bone volume (BV) and bone volume/total volume (BV/TV) in the allograft group, but histology showed no differences in BV or BV/TV between groups. Allograft lacked living cells, whereas autograft was cellularized. No difference was found in maximum removal torque between groups. Compressive loading at the graft‐to‐bone interface was significantly lower in allograft compared with autograft groups. Conclusions: There was less bone in contact with the implant and significantly less maximum compressive load in the allograft group compared with autograft. The allograft remained acellular as demonstrated by empty lacunae. Taken together, block allograft implanted simultaneously with an implant produces a poorer quality bone compared with autograft.